(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate the ambiguities regarding online course of medical sciences from the faculty point of view at Al-Tibri medical college and hospital Karachi. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Al-Tibri medical college and hospital Karachi from February 2020 to June 2020. Materials and Methods: Both genders of basic and clinical sciences were included by non-probability convenient sampling. The faculty was asked to fill the questionnaire. For that a valid questionnaire was adopted, that is based on various questions related with ambiguities of faculty members during online classes. Results: Out of total 50 faculty members (lecturer, assistance professor, associate professor and professor), 58.7% were male and 41.3 females. Most common barriers in Personal obstacles to faculty members' participation in online education were Anxiety regarding excessive workload and insufficient time for other academic activities (68%) in basic and (72%) clinical faculty. Attitudinal and Contextual obstacles to faculty members' participation in online education were facing are anxiety regarding online teaching because of direct proportional effect on quality of education that is due to lack of direct interaction with students (62%) agreed basic (72%) clinical faculty. Conclusion: In present study it was noticed that high percentage of faculty was concerns regarding deficiencies of important equipment like software, internet sources) and inadequate information in online teaching. Thus to implement on new educational environment, need support and training regarding online teaching.